Event-Related Potentials During Decision-Making in a Mixed-Strategy Game - Chang, Fang-Yu; Wiratman, Winnugroho; Ugawa, Yoshikazu; Kobayashi, Shunsuke (Frontiers in Neuroscience, 2021)
The decisions we make are sometimes influenced by interactions with other agents. Previous studies have suggested that the prefrontal cortex plays an important role in decision-making and that the dopamine system underlies processes of motivation, motor preparation, and reinforcement learning. However, the physiological mechanisms underlying how the prefrontal cortex and the dopaminergic system are involved in decision-making remain largely unclear. The present study aimed to determine how decision strategies influence event-related potentials (ERPs). We also tested the effect of levodopa, a dopamine precursor, on decision-making and ERPs in a randomized double-blind placebo-controlled investigation. The subjects performed a matching-pennies task against an opposing virtual computer player by choosing between right and left targets while their ERPs were recorded. According to the rules of the matching-pennies task, the subject won the trial when they chose the same side as the opponent, and lost otherwise. We set three different task rules: (1) with the alternation (ALT) rule, the computer opponent made alternating choices of right and left in sequential trials, (2) with the random (RAND) rule, the opponent randomly chose between right and left, and (3) with the GAME rule, the opponent analyzed the subject’s past choices to predict the subject’s next choice, and then chose the opposite side. A sustained medial ERP became more negative toward the time of the subject’s target choice. A biphasic potential appeared when the opponent’s choice was revealed after the subject’s response. The ERPs around the subject’s choice were greater in RAND and GAME than in ALT, and the negative peak was enhanced by levodopa. In addition to these medial ERPs, we observed lateral frontal ERPs tuned to the choice direction. The signals emerged around the choice period selectively in RAND and GAME when levodopa was administered. These results suggest that decision processes are modulated by the dopamine system when a complex and strategic decision is required, which may reflect decision updating with dopaminergic prediction error signals.